2004
DOI: 10.1016/j.jcrs.2003.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical changes in the anterior lens capsule after trypan blue staining

Abstract: Trypan blue staining of the lens capsule combined with light irradiation for at least 1 minute led to an increase in elastic stiffness at 25% strain and a reduction in the ultimate extensibility. This effect is probably due to the photosensitizing action of trypan blue, leading to light-induced collagen crosslinking of the capsule collagen similar to age-related crosslinking. Nucleus expression might be impeded by the increased capsule stiffness. Continuous curvilinear capsulorhexis is facilitated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 13 publications
0
27
0
3
Order By: Relevance
“…However, little is known on these intrinsic material properties of the native ILM [65]. The epithelial/mesenchymal interface of most tissues is marked by the presence of a basement membrane.…”
Section: Ilm Materials Properties In Chromovitrectomymentioning
confidence: 99%
“…However, little is known on these intrinsic material properties of the native ILM [65]. The epithelial/mesenchymal interface of most tissues is marked by the presence of a basement membrane.…”
Section: Ilm Materials Properties In Chromovitrectomymentioning
confidence: 99%
“…[2][3][4] Trypan blue staining has been used in cell viability assays in the laboratory and recently as a safe and effective method to visualize the anterior capsule during cataract surgery. 2,5,6 Concentrations as low as 0.0125% are also effective in staining the anterior capsule. 7 The concentration of the dye and the time of evaluation of its toxic effect are important.…”
mentioning
confidence: 99%
“…The literature holds little information on the biomechanical changes to the anterior lens capsule caused by trypan blue when it is used to visualize the capsule during capsulorhexis. 5 One study 15 found trypan blue had little cytotoxicity to the lens epithelial cells (LECs) in vitro, irrespective of the dye concentration (from 0.025 to 5.0 mg/mL) and with 806 nm diode laser treatment. We studied the in vivo effect of anterior capsule staining with trypan blue 0.0125% on the density and viability of LECs by comparing eyes with and without trypan blue capsule staining in patients having phacoemulsification by the same surgeon using the same technique.…”
mentioning
confidence: 99%
“…A reduction in the elasticity of the anterior capsule has been reported in studies using human anterior capsule, 54 with a suggestion that this is more significant in diabetic, compared with non-diabetic patients, 55 in a process that appears to be light-exposure dependent. 56 TB has also been reported to stain hydrophilic acrylic IOLs in digital image analysis, but not poly methylmethacrylate or silicone lenses 12 after prolonged exposure of 180 min in in vitro testing. Clinical reports confirm permanent staining of the Acqua hydrophilic expandable acrylic IOL (Mediphacos, Minas Gerais, Brazil), 57 causing a reduction in glare at a mean of 2.6 months post-operatively.…”
Section: Safetymentioning
confidence: 97%